Influence of NaCl solution on dynamic characteristics of clay under cyclic loading and microscopic mechanism analysis - Xinshan ZHUANG; Ruijie PAN; Shunlei XIA (Journal of Hebei University of Science and Technology, 2023)
Aiming at the problem that the change of the pore solution environment has a great influence on the dynamic characteristics of clay, graded loading tests were performed on clay samples under simulated traffic cyclic loads by using a GDS true/dynamic triaxial apparatus. The effects of different concentrations of NaCl pore solution and vibration frequency on the stress-strain relationship and dynamic elastic modulus of the soil were studied, and the development rules of the backbone curve and elastic modulus were analyzed. Combined with electron microscope scanning, the pore distribution law of samples before and after changing the NaCl solution concentration and vibration frequency was analyzed to obtain the relationship between micro-pore size and dynamic characteristics. The results show that with the increase of NaCl solution concentration and vibration frequency, the stress-strain curve and dynamic elastic modulus curve show an upward trend; the damping ratio-dynamic strain curve rises with the increase of vibration frequency and decreases with the increase of NaCl solution concentration; at higher NaCl solution concentration, the increase of colloid produced by the hydration reaction can effectively reduce small pores; increasing vibration frequency compresses the distance between flaky particles, reduces the layered structure and makes the soil more compact, effectively reducing large pores. The influence of pore solution and vibration frequency on clay with NaCl solution is obtained, which provides some reference for intensity change of clay under other environment.